2004
DOI: 10.1152/ajpcell.00553.2003
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular pressure stimulates macrophage phagocytosis by inhibiting a pathway involving FAK and ERK

Abstract: We hypothesized that changes in extracellular pressure during inflammation or infection regulate macrophage phagocytosis through modulating the focal adhesion kinase (FAK)-ERK pathway. Undifferentiated (monocyte-like) or PMA-differentiated (macrophage-like) THP-1 cells were incubated at 37 degrees C with serum-opsonized latex beads under ambient or 20-mmHg increased pressure. Pressure did not affect monocyte phagocytosis but significantly increased macrophage phagocytosis (29.9 +/- 1.8 vs. 42.0 +/- 1.6%, n = 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
66
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 68 publications
(79 reference statements)
6
66
0
Order By: Relevance
“…Propofol does not act via the signal pathways previously reported to mediate the pressure effect on phagocytosis. Previous studies demonstrated that decreasing FAK and ERK activation and increasing the activation of p38 and the PI3K-Akt-p70S6k pathway contribute to the stimulation of macrophage phagocytosis by extracellular pressure (51)(52)(53). We therefore examined the effect of propofol on these signals.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Propofol does not act via the signal pathways previously reported to mediate the pressure effect on phagocytosis. Previous studies demonstrated that decreasing FAK and ERK activation and increasing the activation of p38 and the PI3K-Akt-p70S6k pathway contribute to the stimulation of macrophage phagocytosis by extracellular pressure (51)(52)(53). We therefore examined the effect of propofol on these signals.…”
Section: Resultsmentioning
confidence: 97%
“…We previously reported that increased extracellular pressure (20 mmHg above ambient pressure) stimulates serum-opsonized latex bead uptake by primary isolated monocytes from healthy volunteers as well as PMA-differentiated human monocytic THP-1 cells (THP-1 macrophages) (51)(52)(53). Several reports suggest that anesthetic agents and surgical stress may affect phagocytic cell function (5,23,28) and that tissue pressure may be increased within surgical wounds or at surgical sites postoperatively (56).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations